Preoperative Cardiovascular Assessment in Non-Cardiac Procedure - Wongsinkongman, Chatree (The Journal of Chulabhorn Royal Academy, 2021)
Non-cardiac procedures are performed increasingly every year. As a result, some patients develop cardiovascular complication which ultimately cause morbidity and mortality. Assessing the patients’ risk and optimal preoperative management are the best way to prevent the complication. Nowadays, there are many academic associates launch the perioperative assessment and management guidelines which there are some different details in each guideline, but the overall content remains the same. Each guideline emphasizes on stepwise assessment starting from urgency of procedure, unstable cardiac conditions, procedural cardiovascular risks. If the patients have significant cardiovascular risks and are being performed on quite high surgical risks procedure. They will be further worked up on some laboratory investigation, administering some medication or performing some procedures before. The key point to assess and manage these group of patients is “shared-care-model” which is the consensus between internists, surgeons, and anesthesiologists for the best practice in each patient to reduce cardiovascular morbidity and mortality as much as possible.